Low Turnover of Soil Bacterial rRNA at Low Temperatures - Schostag, Morten Dencker; Albers, Christian Nyrop; Jacobsen, Carsten Suhr; Priemé, Anders (Frontiers in Microbiology, 2020)
Ribosomal RNA (rRNA) is used widely to investigate potentially active microorganisms in environmental samples, including soil microorganisms and other microbial communities that are subjected to pronounced seasonal variation in temperature. This raises a question about the turnover of intracellular microbial rRNA at environmentally relevant temperatures. We analyzed the turnover at four temperatures of RNA isolated from soil bacteria amended with 14C-labeled uridine. We found that the half-life of recently produced RNA increased from 4.0 days at 20°C to 15.8 days at 4°C, and 215 days at −4°C, while no degradation was detected at −18°C during a 1-year period. We discuss the implications of the strong temperature dependency of rRNA turnover for interpretation of microbiome data based on rRNA isolated from environmental samples.